A Retrospective Survey of the Abortion Outbreak Event Caused by Brucellosis at a Blue Fox Breeding Farm in Heilongjiang Province, China - Yulong Zhou; Ye Meng; Yachao Ren; Zhiguo Liu; Zhenjun Li (Frontiers in Veterinary Science, 2021)
Brucellosis is a common zoonosis in China, resulting in abortion in animals. Outbreaks of abortion in blue foxes caused by Brucella infection have rarely been reported. In the present study, 3–5 mL blood samples collected from the femoral veins of 10 abortuses of blue foxes were assessed by RBPT (Rose Bengal plate test) and SAT (serum tube agglutination test) to preliminarily investigate the source of infection for the clustering of abortion events at a blue fox farm in Heilongjiang Province. Screening experiments showed that all 10 blood samples were positive in the RBPT, while only eight blood samples out of the 10 were positive in the SAT. Subsequently, 10 tissue samples (spleen, lungs, stomach contents, and afterbirth) from the same 10 foxes were assessed using AMOS (acronym for B. abortus, melitensis, ovis, and suis)-PCR (polymerase chain reaction), and sequencing analysis was performed on amplification products to verify the results of the serology survey. Results showed a spectral band of ~731 bp in these samples. BLAST showed sequences of AMOS-PCR products in this study to be 100% similar (E = 0.0) to sequences in B. melitensis strain from GenBank. These data preliminarily indicated that the blue fox's outbreak of abortion events was caused by brucellosis via the B. melitensis strain. Then 726 serum samples were tested by RBPT and SAT to determine the prevalence of brucellosis on the farm. A comprehensive epidemiological and reproductive status survey of the infected blue fox population was performed. The seropositive rate was found to be 67.90% (493/726) by RBPT and 41.32% (300/726) by SAT. The technicians had stopped feeding the foxes with chicken carcasses and instead fed them raw ground sheep organs (lungs, tracheae, placentae, and dead sheep fetuses) infected by B. meliteneis strains, and that this change in diet caused the outbreak of abortion events. The high abortion rate (55%) and low cub survival rate (65%) were the most distinctive features of the outbreak; these factors led to severe economic losses. Feeding cooked sheep/goat offal and strict breeding management is necessary for disease prevention.